Integrated dialysis and renal transplantation: small is beautiful. Issue 6230 (21st June 1980) - Nicholls, A J; Catto, G R; Edward, N; Engeset, J; Logie, J R; Macleod, M
Abstract : Many patients in Britain with chronic renal failure suitable for renal replacement treatment die because not enough treatment facilities are available. Moreover, the number of renal transplants performed is insufficient to meet even present needs, so the number of patients on dialysis is rising. The integrated dialysis and transplant unit in Aberdeen, which has a population base much smaller than the average British unit, meets community needs for dialysis and transplantation. The problem of harvesting cadaver kidneys has been solved; the present supply has not only enabled the number of patients on dialysis to remain stable but has resulted in a net export of kidneys. The Aberdeen unit shows how estimated needs for chronic dialysis and renal transplantation may be met.